Low Carbon Operation Optimization of lntegrated Energy System with Reversible Solid Oxide Cell - LI Xin, WANG Changsheng, LI Xinyu, ZHAO Weijie, LI Yang, GUO Panfeng (Dianli jianshe)
Currently，high proportions of renewable energy are consumed by power systems，resulting in increased carbon emissions that adversely affect the environment. To overcomes these challenges，this study proposes to apply a reversible solid oxide cell （RSOC） and a carbon capture system （CCS） to an integrated energy system （IES），dominated by hybrid combined heat and power （CHP） systems，to achieve economic，low-carbon，and flexible comprehensive optimization of the IES. First，the operating mechanism and mathematical models of the RSOC and CCS are constructed. The RSOC is used to store the excess renewable energy for an indefinite period for reuse，thereby alleviating the energy consumption pressure on the CCS during low outputs of wind and solar power. Second，the IES low-carbon economic model of RSOC and CCS is constructed to improve the carbon emission reduction benefit of the model and minimize the economic operation cost. Finally，an improved IEEE-40 node power system in a city in Northwest China is used as an example and seven different configuration scenarios were analyzed. The simulation results show that the model is effective in reducing renewable energy consumption and carbon emission，and it significantly improves the economy and flexibility of IESs.